A high-rate low-enthalpy change modified negative electrode material and its preparation process
By using spherical graphite, modified asphalt and nanoparticles, combined with the combination of modified asphalt and nanoparticles and the three-stage heating carbonization process, the problems of the improvement of performance and reduction of specific surface area of existing graphite negative electrode materials when increasing the magnification and reducing the enthalpy change are solved, and negative electrode materials with high electrical properties and low specific surface area are achieved.
Patent Information
- Application Number
- CN202411051603.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-01
AI Technical Summary
While increasing the magnification and reducing the enthalpy change, it is difficult to simultaneously improve the capacity, first-time efficiency and cycling performance, and the specific surface area is large, affecting battery performance.
Spherical graphite, modified asphalt and nanoparticles are used as raw materials, and the electrical properties of the negative electrode material are improved by combining the low softening point of the modified asphalt and the nanoparticles, and the specific surface area is reduced through a three-stage heating carbonization process.
While achieving high magnification and low enthalpy change characteristics, the electrical properties of graphite negative electrode materials are greatly improved, including gram capacity, first-time efficiency and cycling performance, and the specific surface area is reduced, simplifying the preparation process.
Smart Images

Figure BDA0004975082910000121 
Figure BDA0004975082910000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and in particular to a high-rate low enthalpy change modified negative electrode material and a preparation process thereof. Background Art
[0002] The negative electrode material of lithium-ion batteries is one of the key components of the battery and directly affects the overall performance of the battery, including energy density, cycle life, safety, and charge and discharge rate. With the popularization of portable electronic devices, the rise of electric vehicles, and the growing demand for energy storage systems, the development of high-performance lithium-ion battery negative electrode materials has become a research hotspot.
[0003] Early lithium-ion battery negative electrodes mainly used metallic lithium because of its high theoretical specific capacity and ability to provide extremely high energy density. However, the practical application of metallic lithium faces severe challenges, including safety hazards caused by lithium dendrite growth, low melting point, and adverse reactions with electrolytes, which limit its commercial application. Subsequently, carbon materials, especially graphite, became the mainstream negative electrode materials. Although the theoretical specific capacity of graphite is lower than that of metallic lithium, its volume change during the insertion / deinsertion of lithium is small, its cycle stability is good, and its compatibility with electrolytes is good, which makes graphite-based negative electrodes the first choice for commercial lithium-ion batteries. Carbon materials in different forms, such as artificial graphite, natural graphite, and mesocarbon microbeads (MCMB), have been widely studied and applied to further optimize battery performance.
[0004] But at the same time, graphite negative electrode materials are also facing some technical problems that need to be solved urgently, for example, how to further reduce the specific surface area of graphite negative electrode materials, increase gram capacity, improve the first efficiency and cycle performance, and further improve the rate of negative electrode materials and reduce enthalpy change, which has become a problem that the industry focuses on. Therefore, in order to effectively solve the above problems, the present application provides a high-rate low-enthalpy change modified negative electrode material and a preparation process thereof. The modified negative electrode material prepared in the present application has excellent high-rate and low-enthalpy change characteristics, while further greatly improving the electrical properties of the graphite negative electrode material, including gram capacity, first efficiency and charge and discharge cycle performance, and greatly reducing the specific surface area of the graphite negative electrode material. The preparation process is simple and easy to operate, and has very excellent application and market prospects. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a high-rate low enthalpy change modified negative electrode material. The raw materials include, by mass: 70 to 90 parts of spherical graphite, 5 to 20 parts of modified asphalt, 3 to 8 parts of nanoparticles, and 0.5 to 1.5 parts of dispersant.
[0006] As a preferred solution, the mass ratio of the spherical graphite, modified asphalt and nanoparticles is (7.5-8.8): (1.2-1.8): (0.4-0.7).
[0007] As a preferred solution, the mass ratio of the spherical graphite, modified asphalt and nanoparticles is (7.6-8.5): (1.3-1.5): (0.5-0.6).
[0008] As a preferred solution, the mass ratio of the spherical graphite and modified asphalt nanoparticles is 8.2:1.3:0.5.
[0009] As a preferred solution, the D50 particle size of the spherical graphite is 3.5-7.5 μm.
[0010] As a preferred solution, the D50 particle size of the spherical graphite is 4.5-5.5 μm.
[0011] As a preferred solution, the nanoparticles are at least one of nano-nickel, nano-silicon, nano-cobalt, nano-copper, nano-titanium, nano-zinc, and nano-aluminum.
[0012] As a preferred solution, the nanoparticles are a combination of nano-nickel, nano-silicon and nano-copper.
[0013] As a preferred solution, the mass ratio of nano nickel, nano silicon and nano copper is (3-4): (0.2-0.5): (0.8-1.2).
[0014] As a preferred solution, the average particle size of the nanoparticles is 10 to 40 nm.
[0015] As a preferred solution, the average particle size of the nanoparticles is 20 to 30 nm.
[0016] As a preferred solution, the dispersant is at least one of ethanol, methanol, MF, polyvinylidene fluoride, sodium hexametaphosphate, and hydrogen peroxide.
[0017] As a preferred solution, the dispersant is a combination of ethanol and hydrogen peroxide.
[0018] As a preferred solution, the mass ratio of ethanol to hydrogen peroxide is (4-5):(1.5-2).
[0019] As a preferred scheme, the preparation method of the modified asphalt includes the following steps: S1: mixing medium-temperature coal tar and petroleum asphalt, heating to 120-140°C, mixing and stirring evenly to obtain a mixed asphalt; S2: using n-hexane as a solvent to perform a primary impurity removal on the mixed asphalt by solvent extraction, and then using centrifugal separation to remove high-viscosity residue precipitation for a secondary impurity removal; S3: mixing the impurity-removed mixed asphalt with a modifier and stirring evenly to obtain a modified asphalt precursor; S4: adding the modified asphalt precursor to a reactor, heating to 130-150°C, and keeping the temperature for reaction for 4-8 hours. After completion, adding the modified asphalt precursor to a distiller, increasing the temperature to 180-190°C, and distilling for 3-6 hours, and obtaining it after completion.
[0020] As a preferred solution, the mass ratio of the medium-temperature coal tar pitch to the petroleum tar pitch is (1-2):(7-10).
[0021] As a preferred solution, the mass ratio of the mixed asphalt to the modifier is 100:(10-15).
[0022] As a preferred solution, the modifier is a combination of SBS, SBR and naphtha.
[0023] As a preferred solution, the mass ratio of SBS, SBR and naphtha is (6-8): (3-4.5): (1-2).
[0024] As a preferred solution, the mass ratio of SBS, SBR and naphtha is (7-8): (3.4-4): (1-1.5).
[0025] As a preferred solution, the softening point of the modified asphalt is 100-105°C.
[0026] In this application, by adding the modified low softening point modified asphalt, the electrical properties of the negative electrode material can be greatly improved, the cycle performance of the negative electrode material can be improved, and the specific surface area of the final negative electrode material can be greatly reduced. The modified coated asphalt can be efficiently inserted into the loose pores of the graphite microspheres at a lower temperature through softening, and through high-speed kneading force, the adhesion and encapsulation of the coated asphalt to the graphite microspheres are greatly enhanced during the mixing period, and the high insertion efficiency also greatly reduces the specific surface area of the graphite microspheres at this time, so that the subsequent addition of nano nickel can further promote the mutual penetration between the three molecules, forming a strong van der Waals force, which can form an effective deposition of fixed carbon in a low temperature environment and a short time during the carbonization process, forming an early hard carbon layer.
[0027] The second aspect of the present application provides a preparation process for the above-mentioned high-rate low enthalpy change modified negative electrode material, and the preparation process comprises the following steps: S1: after the dispersant is evenly sprayed onto the surface of the spherical graphite, the dispersant is added into a mixing extruder together, the temperature is increased and the stirring is maintained at 1200-1500 rpm for 3-5 hours; S2: the nanoparticles are added into the mixing extruder and the stirring and extrusion are continued, and the mixture is taken out after being extruded into a sheet; S3: the mixture is added into a carbonization furnace for carbonization, the temperature is increased to 100-105°C at a stable heating rate, the temperature is kept for 1-2 hours, and then the temperature is continuously increased to 900-920°C, the temperature is kept for 1.5-3 hours, and then the temperature is continuously increased to 1200-1400°C, and the temperature is kept for 4-5 hours; S4: after the carbonization is completed, the product is crushed and sieved, and the product is obtained after completion.
[0028] As a preferred solution, the heating rate is 3.5-7°C / min.
[0029] As a preferred solution, the heating rate is 4.5-5°C / min.
[0030] As a preferred solution, the sieve mesh number is 160 to 220 meshes.
[0031] As a preferred solution, the temperature of step S1 is 80-90°C.
[0032] In this application, by controlling the three-stage heating carbonization process in the above-mentioned preparation process and cooperating with the raw material scheme in this application, the electrical properties of the negative electrode material can be greatly improved. In the 100-105°C stage, the addition of modified asphalt with a low softening point can volatilize a large amount of components at this time, forming an effective fixed carbon layer deposition in the early stage, and gradually turning into a hard carbon layer as the temperature rises. In the range of 900-920°C, nickel begins to volatilize components, and can form a metal vapor deposition in the internal pores of the previously formed hard carbon layer, thereby forming a mixed layer that wraps around the hard carbon layer, greatly increasing the strength of the van der Waals force between them, enhancing the strength of the intermolecular interaction, and forming an internal rigid framework structure, which leads to a decrease in resistivity and an increase in conductivity. It is not easily dispersed by the charging and discharging process, and its isotropy is enhanced, which enhances the electron flow rate.
[0033] The beneficial effects of this application are:
[0034] 1. A high-rate, low-enthalpy change modified negative electrode material provided in the present application has excellent high-rate, low-enthalpy change characteristics, while further greatly improving the electrical properties of the graphite negative electrode material, including gram capacity, initial efficiency and charge-discharge cycle performance, and greatly reducing the specific surface area of the graphite negative electrode material. The preparation process is simple and easy to operate, and has very excellent application and market prospects.
[0035] 2. A high-rate low-enthalpy change modified negative electrode material provided in the present application can greatly improve the electrical properties of the negative electrode material, improve the cycle performance of the negative electrode material, and greatly reduce the specific surface area of the final negative electrode material by adding modified low-softening point modified asphalt; the modified coated asphalt can be efficiently inserted into the loose pores of graphite microspheres through softening at a lower temperature, and through high-speed kneading force, the adhesion and wrapping of the coated asphalt to the graphite microspheres are greatly enhanced during the mixing period, and the higher insertion efficiency also greatly reduces the specific surface area of the graphite microspheres at this time, so that the subsequent addition of nano-nickel can further promote the mutual penetration between the three molecules and form a stronger van der Waals force.
[0036] 3. A high-rate, low-enthalpy change modified negative electrode material provided in the present application can greatly improve the electrical properties of the negative electrode material by controlling the three-stage heating carbonization process in the preparation process and cooperating with the raw material scheme in the present application; in the 100-105°C stage, the addition of modified asphalt with a low softening point can volatilize a large amount of components at this time, forming an effective fixed carbon layer deposition in the early stage, and gradually turning into a hard carbon layer as the temperature rises. In the range of 900-920°C, nickel begins to volatilize components and can form a metal vapor deposition in the internal pores of the previously formed hard carbon layer, thereby forming a mixed layer that is mutually wrapped with the hard carbon layer, greatly increasing the strength of the van der Waals force between them, enhancing the strength of the intermolecular interaction, and forming an internal rigid framework structure.
[0037] 4. The purpose of the low enthalpy change in the present invention is to modify the rationality of the distribution of the negative electrode material particles and the vapor deposition of the metal substance inside the graphite to form the best path for electron deintercalation, which has a lower powder resistivity. In a high-rate charge and discharge environment, it effectively suppresses the self-heating of the electrode, thereby achieving a series of processes such as low self-consumption, fast electron input and output, and enhanced cycle performance, which continuously reduce the enthalpy variables and form a better electrochemical reaction effect. DETAILED DESCRIPTION
[0038] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0039] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0040] Example 1
[0041] Embodiment 1 The first aspect provides a high-rate low enthalpy change modified negative electrode material, in which the raw materials include, by mass: 82 parts of spherical graphite, 13 parts of modified asphalt, 0.5 parts of nanoparticles, and 0.8 parts of dispersant.
[0042] The D50 particle size of spherical graphite is 4.8 μm.
[0043] The nanoparticles are a combination of nano-nickel, nano-silicon and nano-copper, the mass ratio of the three being 3.5:0.4:1.1, and the average particle size of the nanoparticles being 24.2 nm.
[0044] The dispersant is a composition of ethanol and hydrogen peroxide, and the mass ratio of the two is 4.5:1.5.
[0045] The preparation method of modified asphalt includes the following steps, calculated by mass: S1: mixing 1.8 parts of medium-temperature coal tar and 8.5 parts of petroleum asphalt, heating to 130°C and stirring the mixture evenly to obtain a mixed asphalt; S2: using 6.5 parts of n-hexane as a solvent to perform a primary impurity removal on the mixed asphalt by solvent extraction, and then performing a secondary impurity removal by centrifugal separation to remove high-viscosity residue precipitation; S3: mixing 100 parts of the mixed asphalt after impurity removal with 12.5 parts of a modifier and stirring the mixture evenly to obtain a modified asphalt precursor; S4: adding the modified asphalt precursor to a reactor, heating to 145°C, and keeping the temperature for reaction for 8 hours. After completion, adding the modified asphalt precursor to a distiller, increasing the temperature to 180°C, and distilling for 4.5 hours, the mixture is obtained after completion.
[0046] Medium-temperature coal tar was purchased from Hebei Tanjiu Energy Technology Co., Ltd. with a softening point of 92°C; petroleum asphalt was purchased from Hebei Tanjiu Energy Technology Co., Ltd. with a softening point of 162°C.
[0047] The modifier is a composition of SBS, SBR and naphtha, and the mass ratio of the three is 7.5:3.5:1.2.
[0048] SBS was purchased from F875 SBS products sold by Guangdong Wengjiang Chemical Reagent Co., Ltd.; SBR was purchased from KR-01 SBR products sold by Shanghai Yuanfeng Plastic Technology Co., Ltd.; and naphtha was purchased from industrial-grade products sold by Shandong Qiansheng Chemical.
[0049] The softening point of modified asphalt is 102.6℃.
[0050] The second aspect of the present embodiment provides a preparation process of the above-mentioned high-rate low enthalpy change modified negative electrode material, and the preparation process includes the following steps: S1: After the dispersant is evenly sprayed onto the surface of the spherical graphite, it is added to a mixing extruder together, the temperature is raised to 88°C and the speed is maintained at 1400rpm for stirring for 4 hours; S2: The nanoparticles are added to the mixing extruder and continued to be stirred and extruded, and the mixture is taken out after being extruded into a sheet; S3: Added to a carbonization furnace for carbonization, the temperature is raised to 98°C at a stable heating rate of 5°C / min, and the temperature is kept for 1.5 hours, and then the temperature is continuously raised to 905°C, and the temperature is kept for 2 hours, and then the temperature is continuously raised to 1300°C, and the temperature is kept for 4 hours; S4: After the carbonization is completed, the product is crushed and sieved through a 180-mesh sieve, and the product is obtained after completion.
[0051] Example 2
[0052] Example 2 The first aspect provides a high-rate low enthalpy change modified negative electrode material, in which the raw materials include, by mass: 88 parts of spherical graphite, 12 parts of modified asphalt, 0.6 parts of nanoparticles, and 0.7 parts of dispersant.
[0053] The D50 particle size of spherical graphite is 4.8 μm.
[0054] The nanoparticles are a combination of nano-nickel, nano-silicon and nano-copper, the mass ratio of the three being 3.8:0.3:1.2, and the average particle size of the nanoparticles being 25.5 nm.
[0055] The dispersant is a composition of ethanol and hydrogen peroxide, and the mass ratio of the two is 4.5:1.5.
[0056] The preparation method of modified asphalt includes the following steps, calculated by mass: S1: mixing 1.8 parts of medium-temperature coal tar and 8.5 parts of petroleum asphalt, heating to 130°C and stirring the mixture evenly to obtain a mixed asphalt; S2: using 6.5 parts of n-hexane as a solvent to perform a primary impurity removal on the mixed asphalt by solvent extraction, and then performing a secondary impurity removal by centrifugal separation to remove high-viscosity residue precipitation; S3: mixing 100 parts of the mixed asphalt after impurity removal with 12.5 parts of a modifier and stirring the mixture evenly to obtain a modified asphalt precursor; S4: adding the modified asphalt precursor to a reactor, heating to 145°C, and keeping the temperature for reaction for 8 hours. After completion, adding the modified asphalt precursor to a distiller, increasing the temperature to 180°C, and distilling for 4.5 hours, the mixture is obtained after completion.
[0057] Medium-temperature coal tar was purchased from Hebei Tanjiu Energy Technology Co., Ltd. with a softening point of 92°C; petroleum asphalt was purchased from Hebei Tanjiu Energy Technology Co., Ltd. with a softening point of 162°C.
[0058] The modifier is a composition of SBS, SBR and naphtha, and the mass ratio of the three is 6.5:4.5:1.
[0059] SBS was purchased from F875 SBS products sold by Guangdong Wengjiang Chemical Reagent Co., Ltd.; SBR was purchased from KR-01 SBR products sold by Shanghai Yuanfeng Plastic Technology Co., Ltd.; and naphtha was purchased from industrial-grade products sold by Shandong Qiansheng Chemical.
[0060] The softening point of modified asphalt is 101.8℃.
[0061] The second aspect of the present embodiment provides a preparation process of the above-mentioned high-rate low enthalpy change modified negative electrode material, and the preparation process includes the following steps: S1: After the dispersant is evenly sprayed onto the surface of the spherical graphite, it is added to a mixing extruder together, the temperature is raised to 88°C and the speed is maintained at 1400rpm for stirring for 4 hours; S2: The nanoparticles are added to the mixing extruder and continued to be stirred and extruded, and the mixture is taken out after being extruded into a sheet; S3: Added to a carbonization furnace for carbonization, the temperature is raised to 98°C at a stable heating rate of 5°C / min, and the temperature is kept for 1.5 hours, and then the temperature is continuously raised to 905°C, and the temperature is kept for 2 hours, and then the temperature is continuously raised to 1300°C, and the temperature is kept for 4 hours; S4: After the carbonization is completed, the product is crushed and sieved through a 180-mesh sieve, and the product is obtained after completion.
[0062] Comparative Example 1
[0063] The specific implementation of this comparative example is basically the same as that of Example 1, except that the raw materials of the high-rate low enthalpy change modified negative electrode material, in parts by mass, include: 70 parts of spherical graphite, 22 parts of modified asphalt, 0.8 parts of nanoparticles, and 0.9 parts of dispersant.
[0064] Comparative Example 2
[0065] The specific implementation of this comparative example is basically the same as that of Example 1, except that the high-rate low enthalpy change modified negative electrode material, in parts by mass, includes: 95 parts of spherical graphite, 6 parts of modified asphalt, 0.8 parts of nanoparticles, and 1.1 parts of dispersant.
[0066] Comparative Example 3
[0067] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified asphalt includes the following steps, measured in parts by mass: S1: mixing 0.5 parts of medium-temperature coal tar and 12.5 parts of petroleum asphalt, heating to 130°C and stirring the mixture to obtain a mixed asphalt; S2: using 6.5 parts of n-hexane as a solvent to perform a primary impurity removal on the mixed asphalt by solvent extraction, and then performing a secondary impurity removal by centrifugal separation to remove high-viscosity residue precipitation; S3: mixing 100 parts of the mixed asphalt after impurity removal with 12.5 parts of a modifier and stirring the mixture to obtain a modified asphalt precursor; S4: adding the modified asphalt precursor to a reactor, heating to 145°C, and keeping the temperature for reaction for 8 hours. After completion, adding the modified asphalt precursor to a distiller, increasing the temperature to 180°C, and distilling for 4.5 hours, the mixture is obtained after completion.
[0068] Comparative Example 4
[0069] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified asphalt includes the following steps, by mass: S1: 1.8 parts of medium-temperature coal tar and 8.5 parts of petroleum asphalt are mixed, the temperature is raised to 130°C, the mixture is stirred evenly, and a mixed asphalt is obtained; S2: 6.5 parts of n-hexane are used as a solvent to perform a primary impurity removal on the mixed asphalt by solvent extraction, and then a secondary impurity removal is performed by centrifugal separation to remove high-viscosity residue precipitation; S3: 100 parts of the mixed asphalt after impurity removal are mixed with 6.5 parts of a modifier and stirred evenly to obtain a modified asphalt precursor; S4: the modified asphalt precursor is added to a reactor, the temperature is raised to 145°C, and the reaction is kept warm for 8 hours. After completion, the modified asphalt precursor is added to a distiller, the temperature is raised to 180°C, and distilled for 4.5 hours. After completion, the modified asphalt is obtained.
[0070] Comparative Example 5
[0071] The specific implementation of this comparative example is basically the same as that of Example 1, except that the modifier is a composition of SBS, SBR and naphtha, and the mass ratio of the three is 3.5:5:4.
[0072] Comparative Example 6
[0073] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the medium-temperature coal tar was purchased from Hebei Tanjiu Energy Technology Co., Ltd. with a softening point of 75°C; the petroleum asphalt was purchased from Hebei Tanjiu Energy Technology Co., Ltd. with a softening point of 132°C.
[0074] The softening point of modified asphalt is 88.2℃.
[0075] Comparative Example 7
[0076] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the preparation process of the high-rate low enthalpy change modified negative electrode material comprises the following steps: S1: after the dispersant is evenly sprayed onto the surface of the spherical graphite, the two are added into a mixing extruder, the temperature is raised to 120°C and the stirring is maintained at 800 rpm for 4 hours; S2: the nanoparticles are added into the mixing extruder and the mixture is continuously stirred and extruded, and the mixture is taken out after being extruded into a sheet; S3: the mixture is added into a carbonization furnace for carbonization, the temperature is raised to 905°C at a stable heating rate of 5°C / min, the temperature is kept for 2 hours, and then the temperature is continuously raised to 1300°C and the temperature is kept for 4 hours; S4: after the carbonization is completed, the product is crushed and sieved through a 180-mesh sieve, and the product is obtained after completion.
[0077] Performance Evaluation
[0078] 1. Electrical performance test: The negative electrode materials prepared in the embodiment and the comparative example were added with a binder and a conductive agent respectively, then stirred and mixed evenly, coated on a copper foil, and dried and rolled at 90°C for 12 hours in vacuum to obtain a negative electrode sheet; the binder was LA132 binder, and the conductive agent was SP; the mass ratio of the negative electrode material, the conductive agent SP, and the binder LA132 was 9.5g:0.2g:0.8g, LiPF6 / EC+EMC+DMC (1:1:1) was used as the electrolyte, the metal lithium sheet was the positive electrode, the diaphragm was Celgard2400 diaphragm, the battery was assembled in an argon-filled glove box, and the electrochemical performance was carried out on a Wuhan Blue Electric CT2001A battery tester, the charge and discharge voltage range was 0.005V~3.0V, and the charge and discharge rate was 1C; the first efficiency and the first discharge capacity were tested respectively, and the test values were taken as the average of 10 tests and recorded in Table 1.
[0079] 2.3C charge and discharge performance: Based on performance test 1, the battery is subjected to a slow charge and discharge cycle with a charge and discharge rate of 0.1C to activate the material and establish the SEI film. Then the battery test system is set to charge and discharge at a rate of 3C; charging stage: charging from low voltage to high voltage cutoff, usually using constant current charging (CC) method; discharging stage: discharging from high voltage to low voltage cutoff, usually using constant current discharge (CC) method, repeat the above charge and discharge process 100 times, record the 3C charge and discharge efficiency, and the battery capacity retention rate after 100 cycles, and the results are recorded in Table 1.
[0080] 3. Specific surface area: The specific surface area of the negative electrode materials prepared in the examples and comparative examples was tested using the usual BET method, and the test values were averaged from 10 tests and recorded in Table 1.
[0081] Table 1 Performance test results
[0082]
[0083]
[0084] It can be seen from the embodiments and comparative examples of the present application and the data results in Table 1 that embodiments 1 and 2 of the present application have obvious advantages over comparative examples 1 to 7 in terms of electrical properties and specific surface area. This is mainly due to the combined effect of the modified coated asphalt added in the present application and the preparation process. Comparative examples 1 to 7 did not adopt the correct limited technical scheme, resulting in obvious differences in their performance. This further proves the necessity of the limited technical scheme in the present application for technical effects and solving technical problems.
Claims
1. A high-rate low-enthalpy change modified negative electrode material, characterized in that: The raw materials include, by weight: 70-90 parts of spherical graphite, 5-20 parts of modified asphalt, 3-8 parts of nanoparticles, and 0.5-1.5 parts of dispersant; The mass ratio of the spherical graphite, modified asphalt and nanoparticles is (7.5-8.8): (1.2-1.8): (0.4-0.7); The D50 particle size of the spherical graphite is 3.5-7.5 μm; The nanoparticles are at least one of nano-nickel, nano-silicon, nano-cobalt, nano-copper, nano-titanium, nano-zinc, and nano-aluminum; The dispersant is at least one of ethanol, methanol, MF, polyvinylidene fluoride, sodium hexametaphosphate, and hydrogen peroxide; The preparation method of modified asphalt comprises the following steps: S1: mixing medium-temperature coal tar and petroleum asphalt, heating to 120-140°C, mixing and stirring uniformly, and obtaining mixed asphalt; S2: using n-hexane as a solvent to perform solvent extraction on the mixed asphalt for primary impurity removal, and then using centrifugal separation to remove high-viscosity residue precipitation for secondary impurity removal; S3: mixing and stirring the impurity-removed mixed asphalt with a modifier to obtain a modified asphalt precursor; S4: adding the modified asphalt precursor to a reactor, heating to 130-150°C, keeping the temperature for reaction for 4-8h, adding the modified asphalt precursor to a distiller after completion, raising the temperature to 180-190°C, distilling for 3-6h, and obtaining the modified asphalt after completion; The mass ratio of the mixed asphalt to the modifier is 100:(10-15); The modifier is a composition of SBS, SBR and naphtha.
2. The high-rate low enthalpy change modified negative electrode material according to claim 1, characterized in that: The nanoparticles are a combination of nano-nickel, nano-silicon and nano-copper.
3. The high-rate low-enthalpy change modified negative electrode material according to claim 2, characterized in that: The average particle size of the nanoparticles is 10-40 nm.
4. The high-rate low-enthalpy change modified negative electrode material according to claim 3, characterized in that: The dispersant is a combination of ethanol and hydrogen peroxide.
5. The high-rate low enthalpy change modified negative electrode material according to claim 4, characterized in that: The mass ratio of the medium-temperature coal tar pitch to the petroleum tar pitch is (1-2): (7-10).
6. The high-rate low-enthalpy change modified negative electrode material according to claim 5, characterized in that: The softening point of the modified asphalt is 100-105°C.
7. The high-rate low enthalpy change modified negative electrode material according to claim 6, characterized in that: The mass ratio of the SBS, SBR and naphtha is (6-8): (3-4.5): (1-2).
Citation Information
Patent Citations
A soft carbon graphite composite anode material, a preparing method and a lithium ion battery
CN106252596A
Coated asphalt and preparation method and device thereof
CN114752397A